Current water main rehabilitation practice using trenchless technology - Yichen Wu (IWA Publishing, 2021)
The market for water infrastructure rehabilitation is growing rapidly due to the increasing age of underground utilities. Currently, two common water main rehabilitation methods exist: cured-in-place pipe (CIPP) and polymer spray-on coatings. CIPP can provide structural support for both internal and external loads, while spray-on techniques provide chemical resistance as well as adding minor strength to the existing pipe. This paper summarizes water main rehabilitation practice using CIPP and spray-on methods. The history of trenchless rehabilitation technology is discussed, as well as current methodologies and products for water mains. The design, installation, and monitoring of water main rehabilitation products are also summarized, along with the associated risks. Quality assurance and control (QA/QC) methods are included for evaluating existing products and procedures. Highlights Summary of the current state of practice of water main rehabilitation using trenchless technology, specifically CIPP and spray-on methods.; Demonstrate the difficulties of water main rehabilitation comparing to sewer pipe rehabilitation.; Illustration of the advantages of using CIPP technology for the rehabilitation of water mains comparing to other methods.;